The Axiological Implementation of Islamic Education in Character Development: A Case Study at Al-Maahira IIBS Malang - Anggraini, Reni Dwi; Prabowo, Dimas Tri; Husna, Rima Lailatul; Kawakib, A. Nurul (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to analyze and describe how the axiology or values of Islamic education play a role in the formation and development of students character within the environment of Al-Maahira IIBS Islamic boarding school in Malang. This research employs descriptive qualitative methods, with data collected through observation, interviews, and documentation. The primary data is derived from observations conducted by the researchers at the research site, supported by secondary data from documents such as lesson schedules, lesson plans, daily journals, attendance records, and profiles obtained from the Al-Maahira website. The results of this study indicate changes or influences from the learning outcomes of religious subjects and the habituation of spirituality by making teachers and musyrifahs as role models in the development of students' character at Al-Maahira IIBS Junior High School in Malang. Students, mostly from financially well-off families and lacking parental attention, present challenges in developing character in accordance with Islamic educational principles. Thus, this research aims to provide contributions to educators, students, and educational policymakers in the process of character formation based on the values and principles of Islamic education. [ Penelitian ini memiliki tujuan untuk menganalisis dan mendeskripsikan bagaimana aksiologi atau nilai pendidikan islam berperan dalam pembentukan dan pengembangan karakter peserta didik dalam lingkungan pondok pesantren Al-Maahira IIBS Malang. Penelitian ini menggunakan penelitian deskriptif kualitatif dengan pengumpulan data menggunakan observasi, wawancara serta dokumentasi, untuk data primer sendiri berasal dari observasi yang peneliti lakukan di lokasi penelitian, serta didukung oleh data sekunder yang berasal dari dokumen-dokumen seperti jadwal pembelajaran, Rencana Pelaksanaan Pembelajaran (RPP), jurnal harian, absensi, serta profil yang dapat peneliti ambil dari website Al-Maahira sendiri. Hasil penelitian ini menunjukkan mengenai adanya perubahan atau pengaruh dari hasil pembelajaran mata pelajaran keagamaan serta pembiasaan sipritualitas dengan menjadikan guru dan musyrifah sebagai role model pada pengembangan karakter peserta didik di SMP Al-Maahira IIBS Malang. Peserta didik yang kebanyakan berasal dari latar belakang keluarga yang berkecukupan secara finansial dan kurang akan perhatian orang tua menjadi permasalahan yang melatarbelakangi adanya karakter peserta didik yang kurang sesuai dengan prinsip pendidikan islam, maka penelitian ini hadir dengan tujuan untuk memberikan kontribusi bagi pendidik, peserta didik, dan pengambil kebijakan pendidikan dalam proses pembentukan karakter peserta didik berdasarkan nilai-nilai dan prinsip pendidikan Islam].